Individuals’ explanations for their persistent or recurrent low back pain: a cross-sectional survey - Setchell, Jenny (BMC Musculoskelet Disord, 2017)
BACKGROUND: Most people experience low back pain (LBP), and it is often ongoing or recurrent. Contemporary research knowledge indicates individual’s pain beliefs have a strong effect on their pain experience and management. This study’s primary aim was to determine the discourses (patterns of thinking) underlying people’s beliefs about what causes their LBP to persist. The secondary aim was to investigate what they believed was the source of this thinking. METHODS: We used a primarily qualitative survey design: 130 participants answered questions about what caused their LBP to persist, and where they learned about these causes. We analysed responses about what caused their LBP using discourse analysis (primary aim), and mixed methods involving content analysis and descriptive statistics to analyse responses indicating where participants learnt these beliefs (secondary aim). RESULTS: We found that individuals discussed persistent LBP as 1) due to the body being like a ‘broken machine’, 2) permanent/immutable, 3) complex, and 4) very negative. Most participants indicated that they learnt these beliefs from health professionals (116, 89%). CONCLUSIONS: We concluded that despite continuing attempts to shift pain beliefs to more complex biopsychosocial factors, most people with LBP adhere to the traditional biomedical perspective of anatomical/biomechanical causes. Relatedly, they often see their condition as very negative. Contrary to current “best practice” guidelines for LBP management, a potential consequence of such beliefs is an avoidance of physical activities, which is likely to result in increased morbidity. That health professionals may be the most pervasive source of this thinking is a cause for concern. A small number of people attributed non-physical, unknown or complex causes to their persistent LBP – indicating that other options are possible.